Childhood Imaginary Companion and Schizotypy in Adolescents and Adults - Zarei, Tohid; Pourshahbaz, Abbas; Poshtmashhadi, Marjan (Journal of Anomalous Experience and Cognition, 2022)
Objective: This study evaluated the association of Childhood Imaginary Companion (CIC) status and schizotypy levels of adolescents and adults within the framework of the Hierarchical Taxonomy of Psychopathology (HiTOP). Method: The sample included 255 Iranian adolescents and adults, grouped according to their CIC status, who responded mostly via e-questionnaires on a website. Schizotypy dimensions were compared between these two groups. Two measures compatible with the HiTOP model were also evaluated both in relation to the short scale of the Oxford-Liverpool Inventory of Feelings and Experiences (sO-LIFE) schizotypy dimensions and the CIC status of participants; one scale used exclusively with adolescents (i.e., the Achenbach System of Empirically-Based Assessment-Youth Self-Report [ASEBA-YSR]), and another with adults (i.e., the NEO-Five Factor Inventory [NEO-FFI]). Results: Scores on the unusual experiences (UnEx) the impulsive nonconformity (ImpNon) dimensions, and the total score of the sO-LIFE were higher for the CIC group. For adolescents, the UnEx dimension and the Thought Problems subscale of the ASEBA-YSR correlated. Scores on three subscales of the ASEBA-YSR (i.e., Thought Problems, Obsessive-Compulsive Problems, and PTSD Problems) were significantly higher for the CIC group. For adults, the neuroticism domain of the NEO-FFI correlated strongly with total score of the sO-LIFE and the cognitive disorganization (CogDis) dimension. This domain of the NEO-FFI was the only one in which CIC adults scored higher than the NIC group. Conclusion: CIC in adolescents and adults is associated with a set of schizotypy dimensions in line with the concept of the “happy schizotype.”